Brunner and Suddarth's textbook of medical-surgical nursing - 4 0 16; Brunner, Lillian Sholtis.;Suddarth, Doris Smith.;Smeltzer, Suzanne C. O'Connell.;Bare, Brenda G.; 5 (Philadelphia, Pennsylvania : Lippincott, 2000)
Accompanying CD-ROM contains a self-study program with questions that review the content covered in Medical-Surgical Nursing.
Includes bibliographical references and index.
System requirements for accompanying computer disk: PC compatible computer; Windows 3.1 or later.
Keywords: 2 -- 0; 6; Nursing.;Surgical nursing.;Nursing Care.;Perioperative Nursing. -- 20; 20; 2